Spectacle Urbanism - Cruz , Douver dos Santos (Revista Nacional de Gerenciamento de Cidades, 2021)
This article addresses the current and rapid transformations that have occurred with the imposition of new "urban consensus" and also the new rules that replaced "modern planning" - strongly characterized by State actions and domination, by strategic or "competitive planning between cities ” which is intended to be flexible, but highly permissible. Therefore, we detect the phenomenon of the glamor of the market economy and the emergence of the unique thinking of cities defined as a kind of common conceptual matrix at the origin of new urban strategies that multiply throughout the world, globalizing and homogenizing cities considering culture as the identity anchor of the new urbanism of the spectacle at the expense of social well-being. Idealizing the new aesthetics of architectures in this new urban scenario grafted on artificialities, we toured cities impacted by calendars of major events, such as the city of Munich, due to the 2006 World Cup, and the city of Rio de Janeiro due to the World Cup in 2014 and the Olympic Games in 2016 successively, to elucidate the purposes of new ventures that excel in intense communication and promotion with a view to building an adequate image for the city through the image making policy or the city marketing strategy launching the city into the world, or rather, selling the city.